Potential of ethyleneproducing pseudomonads in combination with effective N2fixing bradyrhizobial strains as supplements to legume rotation for the control of Striga hermonthica - Ahonsi, M.O.; Berner, D.K.; Emechebe, A.M.; Lagoke, S.T.O.; Sanginga, N. (Elsevier, 2003)
Striga hermonthica (Del.) Benth. is an obligate, root-parasitic, flowering plant that limits cereal production in sub-Saharan Africa.Successful control depends on eliminating its seed reserves in soil, thereby preventing parasitism. Striga hermonthica seeds germinate only if adequately conditioned and exogenous stimulant initiates ethylene production within the seed, or if ethylene is directly supplied to the conditioned seed.Since S. hermonthica is an obligate root parasite, stimulating the seeds to germinate in the absence of the host plants results in seedlings that die within 3–4 days (suicidal germination).Soil injection with ethylene gas is a proven method of eliminating Striga spp.seed reserves in soils, but its cost and potential hazard limit its use in Africa.Use of legume cultivars selected for their ability to cause suicidal germination of S. hermonthica seeds in rotation with cereal host is feasible, but effective reduction of parasite seeds in field soils normally requires several seasons of the legume crop.In this study, ethyleneproducing strains of Pseudomonas sp.in combination with N2-fixing Bradyrhizobia japonicum strains were evaluated in pots as a supplement to legume rotation for S. hermonthica control.Co-inoculating cowpea cv.IT93K-637-1 or soybean cv.SAMSOY-2 with Pseudomonas fluorescens/Pseudomonas putida isolates that do not produce ethylene and with B. japonicum isolates either enhanced or had no effect on nodulation compared with B. japonicum alone.Co-inoculating cowpea or soybean with ethylene-producing Pseudomonas syringae pv. glycinea (Psg) and B. japonicum strains did not affect nodulation.While one or two preceding crops of cowpea or soybean reduced S. hermonthica parasitism on subsequent maize crops, the reductions were significantly improved by coinoculating cowpea or soybean with Psg and B. japonicum strains.Psg and B. japonicum may have reduced S. hermonthica parasitism on maize by causing suicidal germination of S. hermonthica seeds and enhancing N2-fixation.Results indicate that co-inoculating cowpea or soybean with ethylene-producing rhizosphere competent pseudomonads and N2-fixing bradyrhizobia has potential to increase the effectiveness of legume rotation in reducing S. hermonthica parasitism on subsequent maize crops. 2003 Elsevier Science (USA).All rights reserved.